The effect of heat treatment on the open circuit potential of magnesium sacrificial anode - A. M. H., Firdaus; Shaiful Rizam, Shamsudin; Shamsul Baharin, Jamaludin; M. N., Derman; Mohd Fitri, Mohd Wahid; M. Z., Ruhiyudin (University of Malaya, 2010)
Link to publisher's homepage at http://ejum.fsktm.um.edu.my/Default.aspx